THE IMAGE OF INFORMATIONAL SOCIETY IN MODERN SCIENTIFIC NARRATIVES: SOCIO-PHILOSOPHICAL ANALYSIS - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article deals with socio-philosophical analysis of informational society phenomenon in the context of modern scientific narratives.